n → ∞ lim ( n 2 0 1 7 1 2 0 1 6 + 2 2 0 1 6 + ⋯ + n 2 0 1 6 ) = ψ n → ∞ lim ( n 2 0 1 8 1 2 0 1 7 + 2 2 0 1 7 + ⋯ + n 2 0 1 7 ) If above equation holds true we get ψ = 1 + β 1 such that 2 ( β − 1 ) = ϕ ( ϕ + 1 ) .
P = n = 3 ϕ + 1 ∑ ϕ ( n 2 + 3 n + 2 1 ) If P can be represented in the form α δ , then find δ + 1 α .
Details:
ψ ∈ R ; β , ϕ , α , δ ∈ Z .
δ and α are coprime.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For someone not knowing Reimann Sums , one can proove by induction 😛
I just loved the way the problem unfolded encompassing two of pivotal concepts! (+1)
Log in to reply
Ya.... It took a bit of time to design the problem but I'm glad you loved the problem. Go try this too.. ;-p - which is a blend of few concepts of Reimann sums and Properties of Integrations.. You'll surely love it..
Problem Loading...
Note Loading...
Set Loading...
ψ = n → ∞ lim ( n 2 0 1 8 1 2 0 1 7 + 2 2 0 1 7 + ⋯ + n 2 0 1 7 ) n → ∞ lim ( n 2 0 1 7 1 2 0 1 6 + 2 2 0 1 6 + ⋯ + n 2 0 1 6 ) = n → ∞ lim n 1 r = 1 ∑ n ( n r ) 2 0 1 7 n → ∞ lim n 1 r = 1 ∑ n ( n r ) 2 0 1 6 Using Riemann Sums = ∫ 0 1 x 2 0 1 7 ∫ 0 1 x 2 0 1 6 = 2 0 1 7 2 0 1 8 = 1 + 2 0 1 7 1 β = 2 0 1 7 2 ( 2 0 1 7 − 1 ) = 6 3 ( 6 4 ) ⟹ ϕ = 6 3 P = n = 4 ∑ 6 3 ( n + 1 1 − n + 2 1 ) (A Telescopic Series) = 5 1 − 6 5 1 = 6 5 1 2 = α δ ∴ 1 3 6 5 = 5